An investigation into the Vietnamese translation of phrases containing “of” in English literary texts - Lê Quang Hoàng Cương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Translation is a process of substituting a text in one language for a text in another language (Catford. 1965). Translation is thus a replacement process which mainly related to the accuracy, clarity and naturalness of the meaning, ideas or messages of the translation. The paper basically deals with Vietnamese translation of phrases containing OF (PCOs) in English literary work. It attempts to find out the frequent occurrences of applying techniques translation in the process of translation as well as analyze the shifts that occur in the process of rendering English PCOs into Vietnamese. The data of the study were collected from the works of nine famous English literary works and their Vietnamese translation. The finding suggested that six techniques of translation were found in the collected data in which Literal Translation had the highest rate of occurrences while the frequent occurrences of Free Translation recorded the lowest proportion. However, more than one technique of translation may be recorded in a single sample. In order to ensure equivalent effect in the process of translation of PCOs, some kinds of dominant shifts influencing the necessitate alterations in expressing meanings were also analyzed and identified. Unit shifts and Structure Shifts ranks the highest among four kinds of shifts applied. The study has also provided practical implications in foreign language teaching and learning in general, and for the teaching and practice of translation in particular